A review of leishmaniasis: current knowledge and future directions of heterocyclic molecules - Tejaswini Masne; Dileep Kumar; Deepali Bansode (Exploration of Drug Science)
Leishmanial diseases, caused by various species of the protozoan parasite Leishmania, continue to pose a significant global health challenge. Medicinal drugs have been at the forefront of combating these diseases, offering hope for afflicted populations. This review article provides: (1) a comprehensive analysis of current knowledge and the evolving landscape of heterocyclic drug therapies for leishmanial diseases; (2) focusing on the mechanism of drug action; (3) therapeutic effects; (4) side effects; (5) potential future directions. The review begins by outlining the critical importance of heterocyclic drugs in treating leishmanial diseases. It highlights the diverse array of drugs used to combat Leishmania and elucidates the unique mechanisms underlying their efficacy. These mechanisms include disruption of cellular processes within the parasite, interference with DNA replication, and modulation of host immune responses. In addition, the article delves into the effects and side effects of drug therapy, providing an in-depth analysis of their impact on patients. It emphasizes the need for a fine balance between effective parasite clearance and minimizing adverse effects, stressing the importance of continuous research to refine drug regimens and reduce drug resistance. The review also explores various therapies for leishmanial diseases, from chemotherapy to immunotherapy, and discusses their advantages and limitations. Furthermore, it discusses ongoing research efforts aimed at developing novel drug formulations, such as liposomal and nano-carrier-based delivery systems, to enhance drug efficacy and reduce toxicity. This article crucially focuses on future perspectives in heterocyclic drug therapies for leishmanial diseases. It emphasizes the importance of interdisciplinary research and integrating emerging technologies, such as genomics and proteomics, to identify new drug targets and strategies for disease control. The potential for combination therapies and immunomodulators to improve treatment outcomes and combat drug resistance will also discussed.